2020
DOI: 10.5771/0943-7444-2020-4-300
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Organization Systems for the Representation of Multimedia Resources on the Web: A Comparative Analysis

Abstract: The lack of standardization in the production, organization and dissemination of information in documentation centers and institutions alike, as a result from the digitization of collections and their availability on the internet has called for integration efforts. The sheer availability of multimedia content has fostered the development of many distinct and, most of the time, independent metadata standards for its description. This study aims at presenting and comparing the existing standards of metadata, voc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…In addition, Knowledge organization systems aimed at tagging and linking online multimedia resources F I G U R E 1 Representation of digital collections: from metadata to semantic annotation (Catalano et al, 2020;Hyvönen et al, 2016;Lemos & Souza, 2020;Messaoudi et al, 2018;Robledano-Arillo et al, 2020) are designed based on a set of principles and technologies to support the publication of open data on the web, known as linked open data (LOD) (Bizer et al, 2009;Machado et al, 2019), as indicated in Figure 1.…”
Section: Information and Knowledge Organization And Representation In...mentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, Knowledge organization systems aimed at tagging and linking online multimedia resources F I G U R E 1 Representation of digital collections: from metadata to semantic annotation (Catalano et al, 2020;Hyvönen et al, 2016;Lemos & Souza, 2020;Messaoudi et al, 2018;Robledano-Arillo et al, 2020) are designed based on a set of principles and technologies to support the publication of open data on the web, known as linked open data (LOD) (Bizer et al, 2009;Machado et al, 2019), as indicated in Figure 1.…”
Section: Information and Knowledge Organization And Representation In...mentioning
confidence: 99%
“…With the advent of the World Wide Web, known simply as the web and invented in the early 90s by Tim Berners‐Lee, collections of digital objects have grown considerably in their different types, formats, and complexity. In this new multimedia scenario, texts, static, and moving images, videos, sounds, three‐dimensional (3D) models, websites, and other specific media require different forms of processing and representation to link multimedia documents and improve search, browsing, and retrieval systems using aggregating semantic approaches to web resources, in order for users to obtain relevant results (Lemos & Souza, 2020).…”
Section: Information and Knowledge Organization And Representation In...mentioning
confidence: 99%
See 2 more Smart Citations
“…The semantic web has improved the understanding of knowledge representation. It enables computers to comprehend web material and provide a clear meaning in relation to the desired application [9]. By providing high quality video metadata, the semantic web can be searched for information more effectively.…”
Section: Multimedia Metadatamentioning
confidence: 99%